RETRACTED: Effect of secondary material resources on quality indicators of fabric fabrics - Shumkarova Shamsiya; Rajapova Marguba; Ochilov Tulkin (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001